The effect of ambient temperature on the gut microbiota diversity and composition of pied flycatcher (Ficedula hypoleuca) nestlings - Hollmen, Lotta (My University, 2023)
Vertebrate guts harbor a diverse community of microbes, which have significant effects on their host’s body functions. Multiple external and internal factors influence the composition of gut microbiota, but the role of ambient temperature in shaping microbial assemblages is still largely unknown. To shed new light on this topic I explored whether temperature drop changes the diversity and composition of gut microbiota of pied flycatcher (Ficedula hypoleuca) nestlings. In addition to my main interest, temperature effects, I also investigated the role of age, the rearing environment, and genetic background in shaping gut microbiota. The role of environment and genetics was surveyed by conducting a partial cross-fostering experiment for 2 days old nestlings. To examine the temperature effects, the experimental cooling of nest boxes was initiated when nestlings were 7 days old and finished when nestlings were 13 days old. The cloacal swab samples were collected before and after the treatment, and the microbiota was surveyed using 16S rRNA sequencing. The cooling experiment did not influence the diversity or composition of nestlings’ gut microbiota and neither did age, even though the relative abundance of Firmicutes increased with age. The rearing environment explained slightly more the variation in gut microbiota than the genetic background. The lack of effect of the cooling treatment on the gut microbiota diversity and composition might be explained by only a minor change in temperature or quite short cooling period. In addition, uncontrolled factors, such as diet, might override the effects of temperature drop.
Keywords: Avian gut microbiota, Ficedula hypoleuca, temperature effects on microbiota, gut microbiota development, 16S rRNA sequencing